Principals' Perceptions on Managing Private Schools in Kathmandu Valley (Shiksha Shastra Saurabh, 2025)
This is an exploratory qualitative study. It explores the perspectives of principals towards their administrative practices especially in the private schools of Kathmandu Valley. The data collected from ten school principals using semi-structured interviews. The findings have been discussed under the themes like academic leadership, financial management, human resource practices, stakeholder involvement and strategic planning. The principals assert their principalship as a daunting task. The principalship in the private schools in Kathmandu was found to have faced a large range of expectations of the parents, students and teachers. Since there is a large number of private schools, the principalship has to meet highly competitive demands of the stakeholders. Additionally, they ensure a rational balance between affordability on the part of the parents and academic success. There are some key challenges such as allocating adequate resources, inviting professors to ensure expertly support on the part of the teachers and students and preserving a unique institutional character. They were found to have employed strategies to handle these challenges. Some key recommendations have been made in relation to policy, practice and future research.